Public Policy, Educational Quality, and Digital Culture: A Mixed-Methods Analysis of Indonesia’s Intellectual and Technological Gap - Nabila Marsha Safitri; Rizky Wahyu Hijazy; Syaisa Ayurid Mihrain; Muhammad Andi Septiadi; Muhammad Fadhil Hadziq (Tunjuk Ajar: Journal of Education and Culture, 2026)
Indonesia faces two intertwined structural problems: low Programme for International Student Assessment (PISA) scores and slow technological innovation reflected in heavy reliance on imported goods. These are compounded by uneven education-budget distribution and persistent gaps in internet access between Java and the frontier, outermost, and underdeveloped (3T) regions. This study examines how public policy shapes educational quality, digital culture, and technological dependence in Indonesia, and tests whether these problems originate from policy design alone or from interconnected systemic factors. A sequential explanatory mixed-methods design was used. Quantitative data came from 392 respondents across major Indonesian regions (purposive-quota sampling; minimum size benchmarked via Slovin's formula at a 5% error margin), and qualitative data from six semi-structured interviews with students, a teacher, a community member, and a regional parliament member. Content validity was established using Aiken's V (0.81–0.86) and reliability with Cronbach's alpha (0.79–0.84). Analysis applied Thomas R. Dye's Public Policy Theory, linking socio-economic conditions, institutions and processes, and policy outputs. Findings show that low PISA scores, inequitable budgeting, import dependence, and digital inequality are direct consequences of political and policy failures: weak transparency, lax import regulation, and corruption, reinforced by institutional weakness and socio-economic inequality, especially in 3T regions. The study contributes to public policy and education literature by positioning political dynamics as the root cause shaping educational quality and digital culture, and offers targeted instruments for reforming pedagogy, budget governance, and digital inclusion.